CONTENT OF SCIENTIFIC RESEARCH WORK OF THE FUTURE GEOGRAPHY TEACHERS ON THE EARTH SCIENCE STUDY (EDUCATION IN THE 21ST CENTURY, 2023)
The paper identifies the main directions of research activities the future teachers of geography in the study the cycle of the Earth sciences.It is emphasized, for the future teacher of geography the complex of earth sciences takes a leading place in the system of their vocational training and it is basis of their special subject education. The complex of educational disciplines, combining the sciences of the Earth, includes ones such as: "Geology", "Climatology", "Hydrology", "Geomorphology", "Cartography", "Geography of Soils", "Biogeography", "Landscape study", "Geoecology", "Physical geography of mainlands and oceans", "Physical geography of Ukraine", "Regional geography", etc.The goals and general content of these disciplines are revealed; the logic and order of their study are shown. It is substantiated each of these disciplines has a well-organized structure, supported by working programs, teaching materials and training aids, qualitatively new computer-oriented textbooks, atlases, and additional literature.It is analyzed the main forms of the organization of the educational process in the study of the disciplines of the cycle of the Earth sciences; these are namely - lectures, laboratory and practical classes, field practice.It is accentuated on the basic methods of involving students in research activities while the study of physical-geographical disciplines, on the types of research work of students in the classroom and out-of-class time.Modern types of research lectures are described; the contents of laboratory and practical classes using the search methods of students' educational and scientific work are given; the types of field practices in physical geography and the main directions of students' field research are listed; the approaches to the organization of course studies of future teachers of geography are disclosed.The author also serves the system of research work of future teachers of geography while extracurricular time on the example of the experience of Krivoy Rog State Pedagogical University.It is concluded the special work on the part of teachers is need; such one for to shaping a high level of motivation, students' research competence and targeted involvement of students in activity-based modern methods, forms, techniques and technologies for organizing scientific research.
Keywords: students' research activity, methods of teaching geography, researchtraining methods.